Relationship Between the Early Initiation of Substance Use and Attempted Suicide Among in-School Adolescents in Seven Low- or Middle-Income African Countries: An Analysis of the Global School-Based Student Health Survey Data - Li, Lian; Zhao, Yuanzhi; Shi, Meijun; Wang, Yucheng (Frontiers in Psychology, 2021)
Background: Preventing suicide among adolescents is an urgent global public-health challenge, especially in Africa. Accordingly, the aim of this study was to examine the relationship between the early initiation (< 12 years old) of substance use (cigarette smoking, alcohol use, and drug use) and attempted suicide among in-school adolescents in seven African countries. Methods: Data on the early initiation of substance use and on attempted suicide among in-school adolescents over the previous 12 months in Benin, Liberia, Mauritius, Mozambique, Namibia, Seychelles, and the United Republic of Tanzania were collected from Global School-based Student Health Surveys and were pooled to determine the overall prevalence of these behaviors in adolescents. Univariate and multivariate logistic regressions were then performed to evaluate country-specific associations between the early initiation of substance use and attempted suicide in these adolescents, followed by meta-analyses to evaluate overall pooled associations. Results: In the abovementioned seven African low- or middle-income countries (LMICs), overall weighted prevalences of attempted suicide and early initiation of cigarette smoking, alcohol use, and drug use among in-school adolescents were 16.05%, 7.76%, 17.68%, and 3.48%, respectively. Multivariate logistic regression analyses revealed that relative to non-smoking, the early initiation of smoking was significantly associated with attempted suicide in these adolescents [OR (95% CI) = 1.783 (1.219–2.348)]. Additionally, the relationship between early initiation of cigarette smoking and attempted suicide is mostly driven by a higher association in girls [OR (95% CI) = 1.867 (1.031–2.703)] than boys [OR (95% CI) =1.392 (0.995-1.789)]. Moreover, relative to not using other drugs, the early and later initiation of other drug use were also significantly associated with attempted suicide in these adolescents [ORs (95% CIs) = 2.455 (1.701–3.208) and 1.548 (1.198–1.898)]. Conclusion: Programs that can eliminate or decrease the early initiation of substance use among adolescents should be implemented in African LMICs to prevent subsequent suicide attempts, especially among adolescent girls.